Placental villous hypermaturation is associated with idiopathic preterm birth. (12th December 2012) - Morgan, Terry K.; Tolosa, Jorge E.; Mele, Lisa; Wapner, Ronald J.; Spong, Catherine Y.; Sorokin, Yoram; Dudley, Donald J.; Peaceman, Alan M.; Mercer, Brian M.; Thorp, John M.; O'Sullivan, Mary Jo; Ramin, Susan M.; et al.
Abstract: Objective : Pregnancy complications such as intra-amniotic infection, preeclampsia, and fetal intrauterine growth restriction (IUGR) account for most cases of preterm birth (PTB), but many spontaneous PTB cases do not have a clear etiology. We hypothesize that placental insufficiency may be a potential cause of idiopathic PTB. Methods : Secondary analysis of 82 placental samples from women with PTB obtained from a multicenter trial of repeat versus single antenatal corticosteroids. Samples were centrally reviewed by a single placental pathologist masked to clinical outcomes. The histopathologic criterion for infection was the presence of acute chorioamnionitis defined as neutrophils marginating into the chorionic plate. Placental villous hypermaturation (PVH) was defined as a predominance of terminal villi (similar to term placenta) with extensive syncytial knotting. Idiopathic PTB comprised a group without another known etiology such as preeclampsia, IUGR or infection. Results : Acute chorioamnionitis was observed in 33/82 (40%) cases. Other known causes of PTB were reported in 18/82 (22%). The remaining 31/82 (38%) were idiopathic. The frequency of PVH in idiopathic PTB (26/31 = 84%) was similar to cases with IUGR or preeclampsia (16/18 = 89%), but significantly more common than PVH in the group with acute chorioamnionitis (10/33 = 30%) ( p < 0.001). Conclusions : PVH, which is a histologic marker of relative placental insufficiency, is a common finding in idiopathic PTB.